SEWERAGE PUMPING STATION OPTIMIZATION UNDER REAL CONDITIONS - Chabal, Lukas; Stanko, Stefan (GeoScience Engineering, 2014)
Construction of a sewer system on a flat area is characterized by a large number of pumping stations (PS), which implies the probability of occurrence of technical problems and increases operational costs. The article focuses on drainage methods for municipalities situated on a flat area where it is necessary to build up a large number of pumping stations. Problems occur in case of multiple serial, parallel or combined connections of PSs. Energy costs can outweigh other costs, especially if the PS runs more than 2000 hours per year (Wilson et al., 2010). It has been shown that there is a large technical and economic potential for energy savings in sewage pumping. The pumping of waste waters in Slovakia is mostly based on the START-STOP method. This means that the pumps operate at all times at full power. In practice, we can also meet with oversizing of pumps. These and other facts lead to increased power consumption. Also rainwater infiltration and “black” stormwater connections belong to significant present problems in sewer system operation. Large amounts of storm water in a sewerage PS lead to increasing intensity of waste-water pumping, which is reflected in increasing operational costs. Optimization of such sewer system is based on mathematical modelling and was implemented in the “Ivanka pri Dunaji” municipality, close to Bratislava – the capital of Slovakia where the above mentioned problems in wastewater discharge cause considerable operating costs and inefficient performance of the system as a whole for a long time. Due to the enormous houses development, the system is inadequately loaded by rain waters as well. Also poor discipline of property owners contributes to the inauspicious situation to a great extent. Despite a ban of connections, paved areas are drained into the sewage system very often. The identification of such connections is very problematic with regard to ownership rights. Rain waters in sewages can degrade the quality of wastewaters, increase operating costs of pumping and reduce system life cycle. It was demonstrated by mathematical modelling that with the use of information technologies, it is possible to make the existing sewerage systems more effective or propose a new system of pumping and discharging waste waters.